2005
DOI: 10.1128/jvi.79.10.6441-6448.2005
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Is Responsible for Acute Lung Immunopathology but Increases Survival of Respiratory Influenza Virus Infection

Abstract: Interleukin-1␣ (IL-1␣

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
310
3
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(336 citation statements)
references
References 46 publications
14
310
3
9
Order By: Relevance
“…For analysis of primary CD8 + T-cell responses, mice were infected with 0.1 LD50 (1 × 10 7 CFU) of either ΔactA/inlB or ΔactA/inlB L. monocytogenes-L.p.FlaA (both expressing full length OVA and B8R [20][21][22][23][24][25][26][27] epitope) and spleens were harvested on day 7. Spleens were dissociated and red blood cells removed using red blood cell lysing buffer (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For analysis of primary CD8 + T-cell responses, mice were infected with 0.1 LD50 (1 × 10 7 CFU) of either ΔactA/inlB or ΔactA/inlB L. monocytogenes-L.p.FlaA (both expressing full length OVA and B8R [20][21][22][23][24][25][26][27] epitope) and spleens were harvested on day 7. Spleens were dissociated and red blood cells removed using red blood cell lysing buffer (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…4A). It was previously shown that inflammasome-mediated control of infection by influenza virus is partially mediated by IL-1β (25). Additionally, IL-18 has been shown to mediate resistance to variety of pathogens, including Mycobacterium tuberculosis and Shigella flexneri (26,27).…”
Section: Monocytogenes Ectopically Expressing Flagellin Hyperactivatementioning
confidence: 99%
“…Par exemple, au cours de l'infection par le virus de la grippe, la mortalité est supé-rieure chez les souris déficientes en IL-1R ou en IL-18 par rapport aux souris sauvages [42,43]. Par ailleurs, l'infection par le virus herpès de type 1 (HSV1) de souris déficientes en IL-1 résulte en une charge virale sanguine augmentée, un taux d'encéphalites à HSV1 plus élevé, et ce dans un contexte moins inflammatoire.…”
Section: Infections Viralesunclassified
“…Activated caspase-1 cleaves inactive cytokines precursors to a secreted and biologically active form such as IL-1β, IL-18, IL-33 and IL-17. These proinflammatory cytokines further recruit monocytes and neutrophils into the lung to control influenza infection and pathogenesis [71]. Moreover, activation of CD4+ T cells is also mediated by this complex.…”
Section: Dendritic Cell Functional Changes With Agingmentioning
confidence: 99%